Public procurement law in the revitalisation process - Michalak, Magdalena (Transformations of modern cities: Selected trends and instruments, 2022)
Although the regulations in force indicate a whole range of the revitalization stakeholders, the commune plays a key role in this process, and it is responsible for the preparation, coordination and creation of conditions for revitalization. In practice, this task is most often carried out on the basis of the Public Procurement Law, which is associated with the need of following extremely formalized procedures, which sometimes constitutes a significant obstacle for municipalities. However, the Public Procurement Law provides for the possibility of excluding the application of its provisions, provided that the revitalization projects meet the conditions indicated therein. The presented text describes and analyzes the revitalization issues in the above-mentioned context, in particular focusing on the specific rules of public procurement in the Special Revitalization Zone.